Kontribusi mata pencaharian alternatif terhadap pendapatan rumah tangga nelayan: Studi kasus di Kelurahan Bagan Hulu, Kecamatan Bangko, Kabupaten Rokan Hilir, Indonesia - Ilma Amika; Trisla Warningsih; Firman Nugroho (Jurnal Ilmiah Pertanian, 2022)
This study aimed to determine the types of alternative livelihoods carried out by fishermen and analyze the contribution of alternative livelihoods to the total income of fishermen in Bagan Hulu Village. The method used in this study was a survey method. The population in this study was 28 fishermen who have alternative livelihoods, and respondents were taken from the entire population carried out by census. The data collected is primary and secondary data through direct interviews, questionnaires then analyzed descriptively. The types of alternative livelihoods carried out by fishermen in Bagan Hulu Village, Bangko District, Rokan Hilir Regency were blood cockle aquaculture (Anadara granosa), motorcycle repair shops, shrimp paste makers, farmers, laborers/artisans, salted fish managers, and pond security. Alternative work carried out by fisherman households in the fishery and non-fishery sectors contributed enough to the total income, i.e., the primary income of fishermen was 49.33 while alternative work was 50.67%. Nevertheless, there was a need for socialization and training on salted fish processing or other skill from relevant agencies and NGOs that could be used as references for alternative jobs by fishermen during lousy weather.